Event Presentations: Scaling Up Experiential Learning Tools for Sustainable Water Governance in India - Falk, Thomas; Kosec, Katrina; Priyadarshini, Pratiti; Sanil, Richu; Melesse, Mequanint B.; Zhang, Wei; Duche, Vishwambhar; Carrillo, Lucia; ElDidi, Hagar; Foundation for Ecological Security Team (International Food Policy Research Institute, 2023)
As a common pool resource, water is easily depleted if no effective coordination exists among users to ensure provision and regulate withdrawals. The Scaling up experiential learning tools for sustainable water governance in India project aims to enhance sustainable water management at scale by improving the capacities of rural communities to manage water more sustainably.